A human monoclonal antibody based immunoenzymetric assay to measure Fel d 1 concentrations in cat hair and pelt allergenic extracts - Rabin, Ronald L.; Croote, Derek; Chen, Aaron; Dobrovolskaia, Ekaterina; Wong, Joyce Jia Wen; Grossman, Jessica; Hamilton, Robert G. (Frontiers in Allergy, 2024)
In the United States, 19 allergen extracts of different specificities are standardized, which means that their potencies are determined in comparison to a US reference standard. For cat allergen extracts, potency is determined by measuring Fel d 1 content expressed in in Fel d 1 units, and with a unitage that correlates with skin test reactions (bioequivalent allergy units or BAU). Currently, Fel d 1 content is measured with a radial immunodiffusion (RID) assay that uses polyclonal sheep antisera to detect the allergenic protein by producing a white precipitin line in agar gel. However, the RID is considered cumbersome, and the polyclonal sera may qualitatively vary among animals and may recognize epitopes irrelevant to human allergic disease. In this report, we describe a quantitative two-site immunoenzymetric assay (IEMA) for Fel d 1 that uses immobilized capture and soluble biotin-labeled detection Fel d 1-specific human IgE monoclonal antibodies (mAb) that have been class-switched to IgG4. Together, they sandwich Fel d 1 molecules from extracts. Using purified natural Fel d 1 as a calibrator, the historically reported ∼4 micrograms Fel d 1/Fel d 1 unit assignment was directly measured in this mAb-based IEMA at 3.12 ± 0.24 micrograms of Fel d 1 per Fel d 1 unit. This IEMA appears to be equivalent to RID in the measurement of biological potencies of commercial cat hair and cat pelt extracts marketed in the United States.